CZECH INSCRIPTIONS ON VOLHYNIA HEADSTONES: ANALYSIS OF SPELLING AND CONTENT - Vepřek, Miroslav; Zormanová, Michaela (Bohemica Olomucensia, 2021)
Analysis of spelling and content of Czech inscriptions found on the headstones in Volhynia is a part of complex research in the language of Czech speakers settled in this region. The researchers gathered a corpus of 71 inscriptions of various size and contrasted them with a collection published by Česlav Chytrý; his vast database, however, could not be included in the analysis due to unreliable transcriptions and illegible writing on the pictures.The inscriptions show two scripts in use - Cyrillic and Latin. There were 52 instances of predominant Latin script, 16 instances of Cyrillic and 3 hybrid examples. The analysis of grammar and spelling revealed tendencies to non-standard linguistic patterns, e.g., variable vowel length, confusing i/y characters, confusing voiced and voiceless consonants, inaccurate graphemes, and the influence of Ukrainian. Out of 52 Czech inscriptions, only 17 did not contain any non-standard features. Apart from a brief commentary on design of inscriptions, the content analysis focused on personal details of the deceased, their family relations and characteristics which had been appreciated (for instance, the most frequent adjectives were dear, good, and beloved). Moreover, the research reflected on images of death and afterlife grounded in the Christian concepts of life, Purgatory and Heaven. The inscriptions written in verse had been taken mostly from folk poetry, depicting family's grief as well as their hope in an afterlife. Other criteria for analysis included presentation of biographical details which had used both Roman and Arabic numerals and had been influenced by practices typical for Ukrainian.
Keywords: Volhynia region; headstone inscriptions; mixed languages; Czech; Ukrainian; death; religion